A Canonical Trace Associated with Certain Spectral Triples - Paycha, S. (Symmetry, Integrability and Geometry: Methods and Applications, 2010)
In the abstract pseudodifferential setup of Connes and Moscovici, we prove a general formula for the discrepancies of zeta-regularised traces associated with certain spectral triples, and we introduce a canonical trace on operators, whose order lies outside (minus) the dimension spectrum of the spectral triple.